Comparative analysis of the linear dimensions of the ovary, determined using sonography, in an age aspect - A. A. Balandin; A. S. Kobeleva; I. A. Balandina (Сибирский научный медицинский журнал, 2024)
Aim of the study was to carry out a comparative analysis of the linear size of the right and left ovaries, determined using sonography in women in adolescence, the elderly, and old age.Material and methods. The study was based on the results of ultrasound examination of 84 women with normal pelvic dimensions who were examined at the gynecology department of the Perm Krai Clinical Hospital during the period 2021–2022 in order to exclude probable pathology of the reproductive system. Measurement of longitudinal (length), transverse (width), and anteroposterior (thickness) dimensions of the ovary was performed using transvaginal access. Women were divided into three groups: the first consisted of 28 adolescents (16 to 20 years old), the second – 29 elderly persons (56 to 74 years old), the third – 27 seniors (75 to 85 years old).Results. When comparing the indicators of ovarian size, their statistically significant decrease by old age was revealed. Right ovary length from adolescence to the old age decreased by 20.56 % (p < 0.01), left – by 28.62 % (p < 0.01). Right ovarian width becomes smaller by 20.87 % (p < 0.01) in elderly age and by 26 % (p < 0.01) in senile age, left – by 20.8 % (p < 0.01) and by 28.32 % (p < 0.01), respectively, the anteroposterior dimension of the right ovary – by 23.2 % (p < 0.01) and by 38.8 % (p < 0.01), of the left ovary – by 31.19 % (p < 0.01) and by 39 % (p < 0.01), respectively.Conclusions. The results obtained allow us to expand our understanding of the features of the age-related structure of the ovaries and further continue their detailed study, since new knowledge is needed to develop modern methods for the prevention of pathology of the female reproductive system and the timely provision of quality medical care.